2015
DOI: 10.1615/forumimmundisther.2015014226
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Development and Thymic Egress: An Infectious Disease Perspective

Abstract: Emigration of mature naïve CD4 SP T cells from the human thymus to the periphery is not fully understood, although elucidation of the mechanisms that govern egress of T cells is crucial to understanding both basic immunology and the immune response in diseases such as HIV infection. Recent work has brought to light the requirement for sphingosine-1-phosphate (S1P) and its receptors in a variety of fields including mature naïve T-cell egress from the thymus of mice. We are examining the expression and function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 149 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…This is noteworthy, as most studies addressing the expression of autoimmune risk genes investigate blood samples from adult individuals. An interesting instance is SIRPG, a gene associated with type 1 diabetes, which we have previously found to act an expression quantitative loci (eQTL) in human total thymic tissue [20]. Our current data revealed that SIRPG is particularly highly expressed the thymic CD8 + T cells, followed by the infant blood CD4 + and CD8 + T cells.…”
Section: Autoimmune Diseasesmentioning
confidence: 50%
See 1 more Smart Citation
“…This is noteworthy, as most studies addressing the expression of autoimmune risk genes investigate blood samples from adult individuals. An interesting instance is SIRPG, a gene associated with type 1 diabetes, which we have previously found to act an expression quantitative loci (eQTL) in human total thymic tissue [20]. Our current data revealed that SIRPG is particularly highly expressed the thymic CD8 + T cells, followed by the infant blood CD4 + and CD8 + T cells.…”
Section: Autoimmune Diseasesmentioning
confidence: 50%
“…In mice, the T cell egress phenotype has been determined as Cd3 + Cd27 + Cd45ra + Cd62l + Cd69- (20). We found expression levels of SELL (CD62L) generally higher than CD69 in all samples, roughly two-fold, within each dataset (Fig.…”
Section: Markers Of Thymic Egressmentioning
confidence: 75%
“…Tetramers can also be used to further focus the identification of TcR-specific cells in patients restricted to specific HLA alleles (e.g., HLA-A0201). The addition of markers, such as CD45RA, CCR7 and others, can be used to evaluate T-cell maturation states [59].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the T cell egress phenotype has been determined as Cd3 + Cd27 + Cd45ra + Cd62l + Cd69- [21]. In the thymus, CD69 expression has been reported to be downregulated in mature SP thymocytes, enabling expression of S1PR1 and egress from the thymus [22,23].…”
Section: T Cell Egress and Migrationmentioning
confidence: 99%